Effectiveness of Selected Pictographs among Malaysians - Pormalu @ Perumal, Kasturi (2007)
Pictographs are vital when there is a need to communicate in the absence of a common language or script. Generally these pictographs need to be effective in communicating message clearly. However the effectiveness of some pictographs is debatable. This study is designed to measure the effectiveness of selected pictographs through a sample study. The response from the sample is assumed to represent the general public. The pictographs for this study were selected from public places such as LRT station, Kuala Lumpur International Airport (KLIA) and shopping malls. Four (4) hypotheses were developed to measure the effectiveness of the pictographs. Hypothesis one (1) aims to study the significant differences in the answers for each pictographs. The result from hypothesis one (1) shows that pictographs in the study can be grouped into three categories, namely ‘Correctly identifiable’, ‘Incorrectly identifiable’ and ‘Partly identifiable’. Seven (7) out of twenty two pictographs (22) in this study falls under the category ‘Correctly identifiable’ and these pictographs shared common features such as clear picture illustration, common pictographs and found at various public places. Hypothesis two (2) aims to study the association between male and female and their ability to identify the pictographs correctly. The result from this hypothesis shows that there is no significant difference in the ability to identify the pictographs correctly between male and female. iii ABSTRACT Pictographs are vital when there is a need to communicate in the absence of a common language or script. Generally these pictographs need to be effective in communicating message clearly. However the effectiveness of some pictographs is debatable. This study is designed to measure the effectiveness of selected pictographs through a sample study. The response from the sample is assumed to represent the general public. The pictographs for this study were selected from public places such as LRT station, Kuala Lumpur International Airport (KLIA) and shopping malls. Four (4) hypotheses were developed to measure the effectiveness of the pictographs. Hypothesis one (1) aims to study the significant differences in the answers for each pictographs. The result from hypothesis one (1) shows that pictographs in the study can be grouped into three categories, namely ‘Correctly identifiable’, ‘Incorrectly identifiable’ and ‘Partly identifiable’. Seven (7) out of twenty two pictographs (22) in this study falls under the category ‘Correctly identifiable’ and these pictographs shared common features such as clear picture illustration, common pictographs and found at various public places. Hypothesis two (2) aims to study the association between male and female and their ability to identify the pictographs correctly. The result from this hypothesis shows that there is no significant difference in the ability to identify the pictographs correctly between male and female. iv Hypothesis three (3) aims to study the association between race and the ability to identify the pictographs correctly. The result from this hypothesis shows that there is a significant difference in the ability to identify the pictographs correctly among the races. Further analysis for the hypothesis shows that the differences in the ability to identify pictographs among the races can be associated with the occupation category of the respondents. Hypothesis four (4) aims to study the association between education level and the ability to identify the pictographs correctly. The result from this hypothesis shows that there is no association between the level of education and the ability to identify the pictographs correctly. Finally, the study proposes that future refinement for the pictographs, could adapt the elements proposed by the International Standards Organization (ISO) standard, through the ISO 6309 Code.